Impact of Different Amounts of Biochar as Growth Media on Macronutrient Transport Systems of Carrizo Citrange Rootstocks and Related Expression Analysis - Paola Caruso; Maria Patrizia Russo; Maria Allegra; Biagio Torrisi; Giancarlo Fascella; Giuseppina Las Casas; Concetta Licciardello; Marco Caruso; Alessandra Caruso; Filippo Ferlito (Agriculture)
Citrus nurseries significantly increase production costs due to the application of strictly technical and sanitary protocols. The growth media used are generally based on peat, a limited resource that is becoming increasingly scarce and consequently more expensive. Among the alternatives to peat is biochar, which could constitute a valid growing medium component for citrus seedling production. Three growth media were compared, each containing 50% sandy volcanic soil and the remaining 50% being: (i) biochar 50%; (ii) black peat 25% + biochar 25%; and (iii) black peat 25% + lapillus 25% as the control. The impact on the agronomic performance of citrus seedlings was assessed, and the involvement of specific genes in macronutrient uptake was evaluated. Destructive and molecular analyses were performed on leaves and roots during two different periods of the year: February and April. Based on physicochemical parameters and seedling growth, it can be assumed that peat can be partially substituted by conifer wood biochar in a total amount of 25 or 50%. A general comparison of the averages from the sampling and the various analyzed substrates revealed that in February, the evaluated genes involved in the absorption and transport of nutrients were differentially expressed in both leaves and roots, while in April, the expression was not consistent. Additionally, a general comparison between the analyzed tissues showed that, in most cases, expression was higher in the roots than in the leaves. Overall, a comparison among plants grown in different substrates indicated that the medium with 50% biochar displayed the highest expression levels.